Si-Based Anode Materials for Li-Ion Batteries: A Mini Review - Ma, Delong; Cao, Zhanyi; Hu, Anming (Nano-Micro Letters, 2014)
Si has been considered as one of the most attractive anode materials for Li-ion batteries (LIBs) because of its high gravimetric and volumetric capacity. Importantly, it is also abundant, cheap, and environmentally benign. In this review, we summarized the recent progress in developments of Si anode materials. First, the electrochemical reaction and failure are outlined, and then, we summarized various methods for improving the battery performance, including those of nanostructuring, alloying, forming hierarchic structures, and using suitable binders. We hope that this review can be of benefit to more intensive investigation of Si-based anode materials.